ЯКІСНІ ТА ЧИСЛОВІ ПІДХОДИ ДО ДОСЛІДЖЕННЯ НЕЛІНІЙНИХ МАТЕМАТИЧНИХ МОДЕЛЕЙ ТЕХНІЧНИХ КОЛИВАЛЬНИХ СИСТЕМ - ПУКАЧ, ПЕТРО; СЛЮСАРЧУК, ОЛЬГА; ПУКАЧ, ПАВЛО (Herald of Khmelnytskyi National University. Technical sciences, 2024)
У роботі розглянуті важливі класи одновимірних середовищ, згинальною жорсткістю яких можна знехтувати. Застосувати наближені аналітичні методи побудови розв’язків у математичних моделях динамічних процесів у них не вдається. Тому тут дано обґрунтування існування та єдиності розв’язків; проведено якісну їх оцінку; на базі чисельного аналізу підтверджено наведене вище та проаналізовано особливості динамічних процесів деяких із розглядуваних класів систем. In this paper, we consider important classes of one-dimensional media whose bending stiffness can be neglected. It is not possible to apply approximate analytical methods for constructing solutions in mathematical models of dynamic processes in these cases. Therefore, the existence and uniqueness of solutions are substantiated here; their qualitative evaluation is carried out; on the basis of numerical analysis, the above is confirmed and the peculiarities of dynamic processes of some of the classes of systems under consideration are analysed. The technique allows not only prove the correctness of the model solution, but also has an opportunity in its study to apply various approximate methods.